2017
DOI: 10.3892/mmr.2017.7540
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effect of total flavonoids from Ilex pubescens against focal cerebral ischemia/reperfusion injury in rats

Abstract: Ilex pubescens is commonly used in traditional Chinese medicine to treat cardiovascular and cerebrovascular diseases, such as coronary artery disease and stroke. However, the underlying mechanisms remain to be fully elucidated. The aim of the present study was to investigate the effects of Ilex pubescens total flavonoids (IPTF) on neuroprotection and the potential mechanisms in a rat model of focal cerebral ischemia/reperfusion (I/R) injury. Rats were pretreated with intragastric administration of IPTF at dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 63 publications
0
17
0
Order By: Relevance
“…Many studies have demonstrated that activated TLRs in organ injury are associated with oxidative stress ( 41 , 42 ). NO (nitric oxide) is an important inflammatory mediator derived from NOS, including induced NOS (iNOS) and constitutive NOS (cNOS) ( 43 ). Actually, the regulation of NO production by cNOS and iNOS was a complex issue, and it was reported that the activity of cNOS was regulated by LPS and some cytokines in the mouse vascular endothelial cell line ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have demonstrated that activated TLRs in organ injury are associated with oxidative stress ( 41 , 42 ). NO (nitric oxide) is an important inflammatory mediator derived from NOS, including induced NOS (iNOS) and constitutive NOS (cNOS) ( 43 ). Actually, the regulation of NO production by cNOS and iNOS was a complex issue, and it was reported that the activity of cNOS was regulated by LPS and some cytokines in the mouse vascular endothelial cell line ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that the strong inflammatory reaction induced by LPS may decrease cNOS activity in local adrenal gland tissue although ACTH pretreatment alleviates the effect of LPS. NO is predominantly produced by iNOS in the late phase of inflammation ( 43 , 46 ). Here, we found LPS treatment increased levels of iNOS protein secretion in the adrenal gland but decreased T-SOD activity without an ACTH × LPS effect.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the administration of 2′-methoxy-6-methylflavone increases GABA A receptor tonic currents, which are elevated following stroke, through the δ-containing GABA A receptors, decreases infarct volume, and improves functional recovery [141]. Additionally, the administration Ilex Pubescens total flavonoids on neuroprotection using a rat model of focal cerebral ischemia/reperfusion injury has led to a reduction of the neurological deficit score, infarcted area, and brain tissue pathological injury, an increase of the brain-derived neurotrophic factor, glial cell-derived neurotrophic factor and vascular endothelial growth factor expression levels, and a decrease of various proinflammatory cytokines [142].…”
Section: Antioxidants For Neuroprotectionmentioning
confidence: 99%
“…Ilex pubescens was found to reduce IRI in brain’s hippocampus and cortex by down regulation of NO and stimulation of Ca 2+ dependent ATP enzyme activation ( Yan et al, 2017 ). Fang et al (2017) , reported that Ilex pubescens can attenuate the cerebral IRI in MCAO rats. Ilex pubescens inhibited the production of NO due to inhibition of iNOS, cNOS and decreased production of IL-1β and TNF-α.…”
Section: Introductionmentioning
confidence: 99%